2015
DOI: 10.1111/jep.12420
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an integrated syndromic respiratory disease guideline in primary health care settings

Abstract: Training on ISG for respiratory diseases improved the diagnosis of CRD and tuberculosis, and lead to a more rational use of drugs for ARIs in PHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Three intervention studies reported on knowledge of health workers (online supplementary file 4). A before-and-after study in Tunisia found that all general practitioners said the integrated syndromic disease guidelines had improved their knowledge after training but thought the translation of symptoms in Arabic to French could be confusing 37. An evaluation in Kenya found that clinicians had insufficient knowledge about isoniazid preventive therapy for tuberculosis and therefore simple alerts or reminders were inadequate without information on which steps to take 36.…”
Section: Resultsmentioning
confidence: 99%
“…Three intervention studies reported on knowledge of health workers (online supplementary file 4). A before-and-after study in Tunisia found that all general practitioners said the integrated syndromic disease guidelines had improved their knowledge after training but thought the translation of symptoms in Arabic to French could be confusing 37. An evaluation in Kenya found that clinicians had insufficient knowledge about isoniazid preventive therapy for tuberculosis and therefore simple alerts or reminders were inadequate without information on which steps to take 36.…”
Section: Resultsmentioning
confidence: 99%